Optimal plot size in the experiment with low-cold demanding apple trees - Cruz Ribeiro, Gleick; Paiva Carrafa, Militino; dos Santos Bonelá, Édlen; Schmildt, Omar; Czepak, Marcio Paulo; Romais Schmild, Edilson (Revista Ceres, 2024)
Apple cultivation in the tropical conditions in northern Espírito Santo state is recent and, to increase the cropped area, basic field experimentation research is still necessary. Thus, the objective of this work was to determine the optimal plot size (OPS) for experiments with apple plants that are not very demanding in cold conditions of the cultivars Eva, Julieta, and Princesa, based on the evaluation data of three characteristics, in northern Espirito Santo state. After three years and three months, the stem diameter, production in the number of fruits per plant, and mass production per plant were evaluated. To determine the OPS, two methods were used, the maximum curvature modified in its original form, and the maximum curvature modified with bootstrap simulation, both according to Meier and Lessman. The two methods presented similar results for each characteristic, however the productive characteristics presented higher OPS compared to the vegetative characteristic of stem diameter. When setting up field experiments with apple plants of the Eva, Julieta, and Princesa varieties in conditions in the north of the state of Espírito Santo, it is recommended to plan with six plants in each experimental plot.